Preserving Archives - Forde, Helen. (Principles and Practice in Records Management and Archives Ser., 2018)
A brand new and fully updated edition of this seminal work on archival preservation. This book considers the causes of threats to the basic material, outlines the preservation options available and offers flexible solutions applicable in a variety of situations. It offers a wide range of case studies and examples from international specialists.